Fabrication of rGO-GO Long Period Fiber Grating Using Laser Reduction Method - Liheng Chen; Jianhui Yu; Heyuan Guan; Tingting Zhan; Tianjie Rong; Yujia Kong; Wenguo Zhu; Huihui Lu; Jun Zhang; Zhe Chen (IEEE Photonics Journal, 2017)
A laser-reduction technique is investigated to fabricate a novel long period fiber grating (LPFG), whose period is a section of graphene oxide (GO) and reduced graphene oxide (rGO) films on a side polished fiber. Raman spectra, X-ray diffraction, and Fourier transform infrared spectra show that a CW 405 nm laser with low power of only 84 mW is sufficient to fabricate this LPFG by laser-reducing the GO film to rGO film. It is demonstrated that the dip extinction ratio of 15.3 dB can be achieved for such rGO-GO LPFG with a 500 μm period. In addition, it is found that the extinction ratio, full width at half maximum and resonant wavelength of the dip can be optically tuned by the length of LPFG. The work opens a way to implement novel fiber devices based on rGO-GO micro/nanostructure.